The Role of Surgical Androgen Deprivation in the Treatment of Patients With Urine Retention Due to Prostate Cancer - Adil Ibrahim; Fawaz Osman Adam Osman; Siddig Egail; Imad Fadl-Elmula (Sudan Journal of Medical Sciences, 2024)
Abstract Background: Surgical androgen deprivation (SAD) and temporary urethral catheterization remain the most suitable therapy for locally advanced prostate cancer (PC). This study aimed to assess the suitable interval duration for voiding trial without a catheter (TWOC) after SAD and to correlate the Gleason score, prostate volume, and PSA level with the free-catheter voiding success. Methods: A total of 62 patients with urine retention due to PC were included in this study. PSA, pelvic ultrasound, and Gleason score were done prior to SAD as baseline measurements and repeated four weeks after surgery. Initial two-week voiding TWOC was done for all patients and repeated after two weeks for patients who failed the initial voiding TWOC. Results: The results showed that 34 (54.8%) patients had Gleason score > 7, 21 (33.9%) had a score of 7, and 7 (11.3%) had a score < 7. Following SAD, the mean prostate size reduction was seen in 36 (58%) patients, whereas PSA ranged between 0.87 and 38 ng/ml with a mean reduction level of 10.9 ng/ml. All patients with Gleason ≤ 7 could void free one month after SAD. Five patients with Gleason > 7 failed to void free and needed TURP tunneling. In summary, 39 (62%) were void-free after two weeks, 18 (29%) after one month, and the remaining 5 (8.1) required tunneling TURP. Conclusion: The initial TWOC should start two weeks after SAD and followed by a second voiding TWOC two weeks later. Those who fail the second voiding TWOC usually have high Gleason scores, and tunneling TURP may be the best option to treat such patients.